The Influence of Digital Marketing and Customer Relationship Marketing on Consumer Loyalty of HerJamu Products in Bengkalis District - Rini Arvika Sari; Rajabal Akbar (Fakultas Ekonomi Universitas Garut, 2025)
The phenomenon in the industrial revolution 4.0 era shows that more business actors are utilizing digital media as a marketing tool, including HerJamu products in Bengkalis District which optimizes Digital Marketing strategies to strengthen its position in the market. This study aims to determine the effect of Digital Marketing and Customer Relationship Marketing on consumer loyalty of HerJamu products with a sample of 85 respondents taken through accidental sampling techniques. Data analysis was carried out using classical assumption tests, multiple linear regression, and model feasibility tests consisting of coefficients of determination, multiple correlations, F tests, and t tests. The results of the study indicate that Digital Marketing has a positive and significant effect on consumer loyalty, which means that the more optimal the implementation of digital marketing strategies, the higher the consumer loyalty of HerJamu products. In addition, Customer Relationship Marketing has also been proven to have a positive and significant effect on consumer loyalty, so that the better the implementation of customer relationship strategies, the stronger the consumer bond in using HerJamu products in Bengkalis District.